2018
DOI: 10.13187/ejced.2018.1.7
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships between Positive and Negative Perfectionisms, Self-Handicapping, Self-Efficacy and Academic Achievement

Abstract: This research aimed to investigate the relationships between positive and negative perfectionisms, self-handicapping, self-efficacy and academic achievement. For this purpose, an extensive literature review was conducted and a model was suggested. Structural equation model was employed to test the model. The study group of the research consisted of 350 students studying at the Faculty of Muallim Rıfat Education at Kilis 7 Aralık University. The data was collected through positive and negative perfectionism sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 19 publications
0
10
0
4
Order By: Relevance
“…Self-efficacy according to El-Adl and Alkharusi (2020) had a significant positive relationship with learners' academic achievement. Adeoye and Feyisetan (2015) found that learners' academic achievement in the English language was determined by their self-efficacy Similar studies found that learners' academic achievement had a significant positive relationship with their self-efficacy (Bushra & Lubna 2014;Hammed & Toyin 2015;Osenweugwor 2018;Hüseyin, Yıldız & Mehmet 2018;Oyuga, Raburu, & Aloka 2019;Nwaukwa, Onyemechara & Ndubuisi 2019).…”
Section: Discussionmentioning
confidence: 94%
“…Self-efficacy according to El-Adl and Alkharusi (2020) had a significant positive relationship with learners' academic achievement. Adeoye and Feyisetan (2015) found that learners' academic achievement in the English language was determined by their self-efficacy Similar studies found that learners' academic achievement had a significant positive relationship with their self-efficacy (Bushra & Lubna 2014;Hammed & Toyin 2015;Osenweugwor 2018;Hüseyin, Yıldız & Mehmet 2018;Oyuga, Raburu, & Aloka 2019;Nwaukwa, Onyemechara & Ndubuisi 2019).…”
Section: Discussionmentioning
confidence: 94%
“…Another reason for the high level of self-handicapping and anomie scores in both work and transcendence is the nonfunctional perfectionism and self-handicapping (Akar, Dogan, Üstüner, 2018) with the multitude of missions expected from theology (Uçar, 2017). Again, the low autonomy can be one of the explanatory factors of self-handicapping in theologians.…”
Section: Discussionmentioning
confidence: 99%
“…Characterized as a personality disposition, perfectionism is the act of striving for precision and having exceedingly high expectations (Frost et al, 1990). Current evidence suggests perfectionism can be both problematic and beneficial to performance (Martinelli et al, 2017;Akar et al, 2018). For example, Closson and Boutilier (2017) found specific aspects of perfectionism to be associated with procrastination, while other factors were associated with academic engagement.…”
Section: Perfectionismmentioning
confidence: 99%
“…The FMPS consists of six subscales; Concern for Mistakes (CM), Personal Standards (PS), Parental Expectations (PE), Parental Criticism (PC), Doubts about actions (D), and Organization (O). Researcher's find the factors of the FMPS to be associated with either adaptive or maladaptive perfectionism (Stallman and Hurst, 2011;Castro et al, 2017;Akar et al, 2018). Adaptive perfectionism can be thought of as factors that enhance performance, while maladaptive perfectionism hinders performance.…”
Section: Perfectionismmentioning
confidence: 99%
See 1 more Smart Citation